PENGARUH WORD OF MOUTH DAN BRAND COMMUNITY KOMUNITAS SEPAK BOLA DI PEKANBARU TERHADAP BRAND IMAGE - Deny Danar Rahayu (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This research is conducted to analyze the influence of Word of Mouthand BrandCommunity variables both partially and simultaneously towards Brand Image ofInternisti and Romanisti Football Club in Pekanbaru. In this research are threevariables such as Word of Mouth (X1), Brand Community (X2) and Brand Image(Y). The population in this study are all members of the Internisti Community andRomanisti Community in Pekanbaru. The method being used is census with 230active members (101 Internisti Community members and 129 RomanistiCommunity members).Population in this research are 230 active members from cencus method and thedata was taken by giving questionnaires to respondents. Meanwhile, qualitativeand quantitative methods are chosen for data analysis by SPSS version 16.The result of this research shows that Word of Mouth and Brand Communityvariables affect both partially and simultaneously towards Brand Image ofInternisti and Romanisti Football Club in Pekanbaru. Simultaneously independentvariable have positive effect toward dependent variable. But in T testattractiveness Brand Image is most affected positively by Word of Mouth. Thedetermining coefficient (R2) of this research show strong connection betweenindependent and dependent relationshipKeywords ; Word of Mouth, Brand Community and Brand Image